Non-uniform corrosion states of rebar in concrete under chloride environment. (April 2015) - Muthulingam, S.; Rao, B.N.
Highlights: A numerical framework for quantifying non-uniform corrosion penetration depth is presented. Effects of rebar size and location on the process of chloride ingress into concrete are emphasized. Non-uniform corrosion states designating the spatial distribution of corrosion penetration depths are proposed. Qualitative comparisons of the evaluated non-uniform corrosion states are presented. Abstract: This study proposes and verifies a numerical framework that can efficiently quantify non-uniform corrosion penetration depth along the perimeter of the rebar in concrete exposed to chloride environment. Moreover, this framework considers the effects of rebar size and location on the process of chloride ingress into concrete and evaluates the non-uniform corrosion states that correspond to two scenarios of corrosion penetration depth: corrosion of segment of the rebar and uneven corrosion along the rebar perimeter. Qualitative comparisons of the evaluated non-uniform corrosion states with the variety of available laboratory and field data show good agreement.